Incentivos fiscais e sua influência no valor adicionado produzido pelas empresas - Lima, Lauro Vinício de Almeida (2017)
In the midst of a broad discussion about the efficiency of the use of fiscal incentives as an instrument of economic intervention by the State, this research brings new perspectives to the subject, verifying, in the publicly traded companies listed in the Brasil Bolsa Balcão (B3), over the years from 2010 to 2016, what influence of the tax incentives in the generation of wealth produced by the companies. At this point, given the importance of the added value produced by companies for the analysis of the effectiveness of tax incentives, in the face of national and international studies related to the subject, the research was based on the elasticity theories of tax revenue, agency and the tax incentives, through the tax burden, in the added value produced by the companies. To solve the research problem, a regressive model was used in which the dependent variable is the percentage added value produced on the revenues and the independent variables are: the percentage of the taxes paid by the company on its revenues, as proxy of the tax burden; And fiscal incentives, a dummy variable where 1 has and 0 has no incentives. The control variables used in the model were: the economic recession that reached Brazil between the years 2014 to 2016, the size and leverage of the companies. The empirical evidence found supports the hypothesis that tax incentives, through fluctuations in the tax burden, negatively influence the value added produced by the companies. At this point, the research contributes to the academy by theoretically discussing and bringing empirical evidence that reducing the tax burden, through fiscal incentives along the lines offered in Brazil, may jeopardize the process of wealth generation by Brazilian publicly traded companies, in an analysis relevant to society in general, because it is necessary to maximize and protect the process of adding wealth by companies, because the resources shared in the economy of a country depends on this process. The findings rekindle the discussion about the usefulness of fiscal incentives for the economy and society, as well as to point out the importance of an effective follow-up of the fruition of the tax benefits obtained by the companies and their consequence for wealth generation.